2002
DOI: 10.1002/joc.774
|View full text |Cite
|
Sign up to set email alerts
|

Parameterization of effective ice particle size for high‐latitude clouds

Abstract: A parameterization has been developed for mean effective size D ge in terms of ice water content (IWC) and temperature using in situ measurements of ice crystal spectra, cloud particle shapes and particle cross-sectional area A from four research projects conducted in latitudes north of 45°N. The cloud microphysical measurements were made using PMS 2D optical probes, a PMS forward scattering spectrometer probe (FSSP), and Nevzorov total water and liquid water content probes. The IWCs derived from particle spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
67
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 41 publications
(60 reference statements)
7
67
3
Order By: Relevance
“…For ST-HICs with the same IWP, we recognize even a different behaviour of D e with T cld : it increases in the tropics whereas it decreases in the midlatitudes. Previous studies (Ivanova et al, 2001;Boudala et al, 2002;Edwards et al, 2007) used the temperature to parameterize D e . We found that these parameterizations, generally established for clouds warmer than 230 K, underestimate D e by about 10 to 20 µm compared to our data (not shown).…”
Section: E Parameterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…For ST-HICs with the same IWP, we recognize even a different behaviour of D e with T cld : it increases in the tropics whereas it decreases in the midlatitudes. Previous studies (Ivanova et al, 2001;Boudala et al, 2002;Edwards et al, 2007) used the temperature to parameterize D e . We found that these parameterizations, generally established for clouds warmer than 230 K, underestimate D e by about 10 to 20 µm compared to our data (not shown).…”
Section: E Parameterizationmentioning
confidence: 99%
“…5), another sign that the dependence on IWP is better suited to parameterize D e (Baran et al, 2009). Compared to a parameterization developed for in situ measurements at a specific latitude band as for example by Boudala et al (2002), it seems to be difficult to determine a global multivariate parameterization for D e dependent on both IWP and temperature, because the latter is not independant as can be seen in Fig. 5.…”
Section: E Parameterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Different parametrizations of effective ice crystal radius as a function of ice water content. The parametrizations were taken from Lohmann and Roeckner (1996), McFarlane et al (1992), Boudala et al (2002), and Sun and Shine (1994). For those parametrizations that depend on temperature in addition to the ice water content, two different temperatures (−40°C and −70°C) were applied.…”
Section: Requirements On Iwpmentioning
confidence: 99%
“…D eff values in Table 6 were estimated using a definition given in Fu (1996) which uses particle cross-section area. The uncertainty in D eff , due to many small ice crystals probably existing at sizes less than 100 µm, can be as high as 50% (Boudala et al, 2002).…”
Section: Relationship Between Cloud Microphysics and The Arctic Oceanmentioning
confidence: 99%